Implementasi Algoritma Vigenère Cipher pada Sistem Absensi Berbasis Web Menggunakan Metode Agile - Cahya, Ersya Dwi; Rodianto, Rodianto (Universitas Multi Data Palembang, 2025)
The rapid development of information and communication technology has significantly impacted various sectors, including business operations. However, challenges in securing sensitive data have become increasingly critical, particularly for organizations like PT Sinar Bali. The company faces issues with its manual attendance system, including inefficiencies, data processing delays, and risks of data breaches. To address these problems, this study developed a web-based attendance system integrated with the Vigenère Cipher algorithm to enhance data security and operational efficiency. The Vigenère Cipher provides a lightweight and effective encryption solution for protecting sensitive information such as employee names and identification numbers (NIK). The system was developed using PHP, the CodeIgniter framework, and MySQL database, employing Agile methodology. Black-Box testing confirmed the system's functionality, demonstrating seamless login, employee data management, attendance recording, and navigation. Real-time encryption ensures data security without compromising performance, with query execution times averaging 0.0004 seconds. This system meets all specified criteria, is ready for real-world implementation, and contributes to advancing secure information systems. Future enhancements may include two-factor authentication and automated reporting features to further optimize system functionality